The tuning of temperature stability in ultralow loss (Ba/Sr) zirconate microwave dielectric - Pulphol, Phieraya; Vittayakorn, Wanwilai; Bongkarn, Theerachai; Kolodiazhnyi, Taras; Pongampai, Satana; Maluangnont, Tosapol; Vittayakorn, Naratip (My University, 2022)
The ceramic composition of Ba1-x Sr x (Zr0.96Ga0.02Nb0.02)O3, where x = 0, 0.1, 0.2, 0.4, 0.5, 0.7, 0.9 and 1, was prepared and its crystal structure, microstructure, Raman and dielectric properties are analyzed. As revealed by powder x-ray diffraction analysis, the crystal structure transforms from cubic (Pm-3m) at 0 ≤ x ≤ 0.2 via tetragonal (Cmcm) at 0.2 < x ≤ 0.5 to orthorhombic (Pbnm) at x > 0.5. This is in agreement with the structural transformations previously reported for the Ba1-x Sr x ZrO3 and Ba1-x Ca x ZrO3 solid solution systems. Raman spectroscopy consistently supports these findings. The effects of structural distortion, grain size and density of samples on the microwave dielectric properties are discussed. With increasing Sr content from x = 0 to 0.2, the Q-factor of Ba1-x Sr x (Zr0.96Ga0.02Nb0.02)O3 ceramics drastically decreases from 18,000 to 3,000 at 10 GHz. The ceramics with a temperature coefficient of −1.4 ppm/K, dielectric constant of 37 and Q-factor of 2,900 at the resonant frequency f = 10 GHz was obtained at x = 0.5.
Keywords: BaZrO3; Microwave dielectric; structural distortion; temperature coefficient of resonant frequency